Penerapan Metode Contextual Teaching and Learning (CTL) Berbantuan Media Kotak Misteri (KOMIS) Untuk Meningkatkan Minat Belajar Siswa Kelas 2 SDN Mergosono 1 Malang - Andi Wibowo; Ricky Wahyu Pradana (Jurnal Multidisiplin Madani, 2022)
This study aims to increase students' interest in learning Contextual Teaching and Learning (CTL) assisted by mystery box-based learning media (komis) in grade 2 students of SDN Mergosono 1 Malang. The type of research used is classroom action research. The subjects of the research were 22 students in class II SD Negeri 1 Mergosono Malang. The research was carried out in two cycles, in each cycle planning, action, observation and reflection were carried out. Data collection techniques in this study used student interest questionnaire sheets, student response questionnaire sheets, CTL learning implementation observation sheets, and student learning interest observation sheets. The score in the first cycle showed that 4 students had interests below 70% of the total 22 students, so that the average interest of grade 2 students was 81.81%. In the second cycle, it showed 1 student who had an interest below 70% of the total 22 students, so that the average interest of grade 2 students was 95.4. From the data obtained, the application of the Contextual Teaching and Learning (CTL) method assisted by mystery box-based learning media (komis) can increase the learning interest of grade 2 students at SD Negeri 1 Mergosono Malang.